Attracting and Retaining Young Workforce in Indonesia: Does Person-Organization (P-O) Fit Matter? - Sartika, Dina (UI Scholars Hub, 2019)
Rooted in the similarity−attraction−attrition paradigm, Cable and Judge’s framework has been one of the leading models in explaining Person−Organization fit. It associates perceived value congruence with employee work attitudes pre and post their entry. This study extends the model and findings by looking at the specific, underlying value dimensions that cause these effects. Drawing on a sample of 800 Indonesian jobseekers, I applied polynomial regression to test the model. Results showed that congruence between personal and organizational social responsibility value was the strongest and most consistent dimension predicting employee job satisfaction and organizational commitment.